Mapping social exclusion in India: caste, religion and boderlands - Judge, Paramjit S. (ed.) (New Delhi, 2014)
This book assesses the problem of defining exclusion, highlights the need for its contextualisation and establishes a relationship between social exclusion, deprivation and discrimination. It studies the complex mosaic of Indian systems and society, marked with exclusionary practices and structures on the basis of caste. It presents grassroots level information through empirical investigations and studies how physical spaces become sites of exclusion when borders become volatile. Scholars put together their diverse research, studies, perceptions and ideas and, most importantly, their years of expertise to focus on a central theme of social exclusion in Indian society. They study the role of the state as an interventionist force and look into the political mobilisation strategy as a reaction to exclusion. The book also takes a critical look at the reservation policy and argues that state intervention creates certain new forms of exclusion.
Keywords: Marginality; Social-India